The management of gout in different clinical specialties in Turkey: a patient-based survey. Issue 12 (December 2016) - Öztürk, Mehmet; Mercan, Rıdvan; Gök, Kevser; Onat, Ahmet; Kısacık, Bünyamin; Kimyon, Gezmiş; Balkarlı, Ayşe; Kaya, Arif; Çobankara, Veli; Balcı, Mehmet; Pamuk, ÖmerNuri; Yıldırım Çetin, Gözde; et al.
Abstract Although gout is potentially curable, the management of this disease is often suboptimal. In this study, we investigated the treatment of gout in Turkey and also compared the management approaches to gout in different clinical specialties. Three hundred and nineteen consecutive patients (mean age 58.60 ± 12.8 years; 44 females, 275 males) were included in this multicenter study. A standardized form was generated to collect data about the patient's first admission to health care, the specialty of the doctor first diagnosed the gout, the treatment options for gout including attack management, patient referral, chronic treatment including medical treatment, and life style modifications. Forty patients were referred to another center without any treatment (12.8 %), and referral rate is most common among the primary care physicians (28.8 %). Colchicine was more commonly used for attack prophylaxis than allopurinol. Ninety-two patients had never been treated with allopurinol (28.8 %). Allopurinol prescription was less common among the primary care physicians and orthopedists, and highest among the rheumatologists. Recommendation of diet and life style modifications was less common among the primary care physicians and orthopedists, and highest among the rheumatologists. The rates of life style modification recommendation and long-term allopurinol prescription were 83.7 and 77.6 %, respectively, among the rheumatologists. Both acute and chronic management of gout is suboptimal in Turkey especially among the primary care physicians and orthopedists. Moreover, chronic treatment is even suboptimal among rheumatologists.